OPTIMIZATION OF CO2, FIBER AND DIODE LASER PARAMETERS FOR MARKING AND CUTTING THE CORK - Adijāns, Imants; Kažmere, Ieva; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Nowadays, lasers are trying to use as many different industries and processes as possible due to their characteristics. One of the main uses of lasers is the cutting and marking of materials. The most common laser processed materials is wood and metal. Cork is one of the safest and easiest materials to process with laser but compared to wood and metal it is more difficult to predict the end result due to this material non-homogeneity. This study is explored natural cork processing and set optimal parameters to get the best results for cutting and marking with lasers. The essence of the research is to prove that it is possible to get good results in cork laser treatment and that there is a prospect of future processing of cork and similar materials with laser devices. There was made 1260 measurements of laser processing on cork, data was collected and graphs plotted and analysis of collected data was made as well.